Isolamento, identificação e antagonismo de fungos endofíticos de Eremanthus sp - Godinho, Bárbara Temponi Vilarino (2016)
Many plants live in symbiosis with microorganisms that can live on their surface (epiphytic) or interior (endophytic). Many of these microorganisms produce secondary metabolites that can protect the plant or induce some host defense response. Moreover, the microorganisms that produce such substances have been explored as biocontrol agents against insects, weeds, plant pathogenic fungi and pathogenic bacteria. Thus, the aim of our study was to isolate endophytic fungi Eremanthus sp. and check if they have antagonistic activity against fungal pathogens of plants and pathogenic bacteria. The endophytic fungi were isolated from three areas of the Serra da Bocaina in Minas Gerais, in three different conditions; with human interaction (Area 1), in their natural habitat (Area 2) and in planned planting (Area 3). The endophytic fungi found were identified by sequencing of the ITS region and subjected an in vitro antagonism test. The antagonisms that show antibiosis were submitted to tests on split plates to verify the volatile compound production. In the test against bacteria, filtrates of each endophytic fungus were separated and applied in the disk diffusion method. Endophytic fungus filtrate showed no inhibitory action against bacteria. In the pairing of endophytic fungi against the pathogens used fungi of the gerera Cryptosporiopsis, Diaporthe, Xylaria, Paraconiothirium and Camarosporium presented antibiosis by releasing compounds in the medium. This paper is the first report on the isolation of twelve genera in Eremanthus sp. besides verifying their antagonist capacity such fungi, which opens the way for the discovery of the substances produced by the endophytic fungi that inhibit pathogens.